Severe Sepsis and Septic Shock Associated with Chikungunya Fever in an Adolescent. (6th January 2018) - Sharma, Pradeep Kumar; Kumar, Maneesh; Bhandari, Neha; Kushwaha, Anand
Abstract: Chikungunya is usually a benign disease, and little is known on the occurrence of severe clinical complications. We describe a 12-year-old boy with rapid onset septic shock and multi-organ failure associated with chikungunya fever. Severe sepsis and septic shock can be associated with chikungunya.